M= 512 - \(\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-...-\frac{512}{2^{10}}\)
=> 2.M = 1024 - 512 - \(\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-...-\frac{512}{2^9}\)
=> 2.M - M = 1024 - 512 - 512 + \(\frac{512}{2^{10}}\)
=> M = \(\frac{512}{2^{10}}=\frac{2^9}{2^{10}}=\frac{1}{2}\)
M = \(512-\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-.....-\frac{512}{2^{10}}\)
M = \(512-512.\left(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{10}}\right)\)
Đặt A = \(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{10}}\)
2A = \(1+\frac{1}{2}+\frac{1}{2^2}+....+\frac{1}{2^{11}}\)
A = 2A - A = \(1-\frac{1}{2^{10}}\)
=> M = \(512-512.\left(1-\frac{1}{2^{10}}\right)\)
=> M = 512.\(\left(1-1+\frac{1}{2^{10}}\right)\)
=> M = \(512.\frac{1}{2^{10}}\)
=> M = \(\frac{512}{2^{10}}\)
\(M=512-\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-...-\frac{512}{2^{10}}\)
\(\Rightarrow\frac{1}{2}M=\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-\frac{512}{2^4}-...-\frac{512}{2^{11}}\)
\(\Rightarrow M-\frac{1}{2}M=512-\frac{512}{2}-\frac{512}{2^2}-\frac{512}{2^3}-...-\frac{512}{2^{10}}-\frac{512}{2}+\frac{512}{2^2}+\frac{512}{2^3}+\frac{512}{2^4}+...+\frac{512}{2^{11}}\)
\(\Rightarrow\frac{1}{2}M=512-\frac{512}{2}-\frac{512}{2}-\frac{512}{2^{11}}=-\frac{512}{2^{11}}\Rightarrow M=-\frac{512}{2^{11}}.2=-\frac{512}{2^{10}}\)